ADE612 - Interactive Multimedia Design and Production / Faculty of Education - UiTM, Faculty of Education (Universiti Teknologi MARA (UiTM), 2023)
This course provides students a hands-on experience with high-end technology in the marketplace and its application in information technology. A wide range of current hardware, software and applications will be explored. Students will use their creativity and skills to design, and create interactive multimedia presentations, digital images, sound, and videos, and will be introduced to animation and web pages. Emphasis will be given on producing an innovative and functional interactive multimedia application. The course stimulates the practice in the multimedia industry. Knowledge and skills acquired in this course will also enable students to successfully perform and interact in today’s technology-driven society.